2015
DOI: 10.1002/tox.22175
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of intrinsic and extrinsic apoptotic pathways in zearalenone-treated rat sertoli cells

Abstract: Zearalenone (ZEA) is a nonsteroidal estrogenic mycotoxin produced mainly by Fusarium. ZEA causes reproductive disorders and is both cytotoxic and genotoxic in animals; however, little is known regarding the molecular mechanism(s) leading to ZEA toxicity. Sertoli cells are somatic cells that support the development of spermatogenic cells. The objective of this study was to explore the effects of ZEA on the proliferation, apoptosis, and necrosis of rat Sertoli cells to uncover signaling pathways underlying ZEA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 38 publications
1
20
0
2
Order By: Relevance
“…These include supporting structural stability, providing nutrients and synthesizing other essential elements for germ cells, and constructing the blood-testis barrier (BTB) (Cheng and Mruk 2012). Therefore, any damage to Sertoli cells will severely impact spermatogenesis (Xu et al 2015). Sertoli cell apoptosis mainly involves FasL-dependent, direct or indirect regulation of the intrinsic and extrinsic apoptotic pathways (Xu et al 2015).…”
Section: Regulation Of the Fas/fasl Signaling Pathway In The Sertoli mentioning
confidence: 99%
See 1 more Smart Citation
“…These include supporting structural stability, providing nutrients and synthesizing other essential elements for germ cells, and constructing the blood-testis barrier (BTB) (Cheng and Mruk 2012). Therefore, any damage to Sertoli cells will severely impact spermatogenesis (Xu et al 2015). Sertoli cell apoptosis mainly involves FasL-dependent, direct or indirect regulation of the intrinsic and extrinsic apoptotic pathways (Xu et al 2015).…”
Section: Regulation Of the Fas/fasl Signaling Pathway In The Sertoli mentioning
confidence: 99%
“…Therefore, any damage to Sertoli cells will severely impact spermatogenesis (Xu et al 2015). Sertoli cell apoptosis mainly involves FasL-dependent, direct or indirect regulation of the intrinsic and extrinsic apoptotic pathways (Xu et al 2015). On the one hand, FasL induces caspase-8 activation of the extrinsic apoptotic pathway, followed by activation of the caspase-3, −6, −7 cascade reaction, leading to cell apoptosis; on the other hand, activation of caspase-8 contributes to the Bax/Bcl-2 reaction of the intrinsic apoptosis pathway and initiates caspase-9, caspase-3 signal to induce apoptosis (Hengartner 2000).…”
Section: Regulation Of the Fas/fasl Signaling Pathway In The Sertoli mentioning
confidence: 99%
“…ZEA could induce cell apoptosis in porcine granulosa cells through the mitochondrial and caspase-dependent pathway [ 18 ]. ZEA could also affect the expressions of Bcl-2 family proteins including up-regulating Bax and down-regulating Bcl-2 expression [ 90 , 91 ].…”
Section: The Molecular Mechanisms Of Zea Caused Cell Deathmentioning
confidence: 99%
“…Robeva et al [64] have also reported, through clinical trials, that Sertoli cell function is suppressed in MetS. As Sertoli cells support and provide nutrition for the developing germ cells and are absolutely necessary for proper germ cell development and viability [55], Sertoli cell dysfunction reduces supportive capacity and impairs spermatogenesis and fertility [85]. Sertoli cell changes may also explain the abnormal presence of spermatids near the basement membrane as reported by Russell et al [65] who suggested spermatids' phagocytosis by Sertoli cells and, then, failure of release.…”
Section: Discussionmentioning
confidence: 99%